Psychometric Evaluation of a Modified Medication Adherence Scale for People Living with HIV: Evidence From a Multisite Study - Nurtanti, Susana; Handayani, Sri; Husna, Putri Halimu (An Idea Health Journal, 2025)
Introduction:Medication adherence critically determines treatment success among people living with HIV (PLHIV), especially in achieving optimal outcomes from antiretroviral therapy (ART). However, accurately measuring adherence remains challenging due to behavioral, psychological, and contextual barriers influencing patients’ medication-taking practices. Reliable and valid measurement instruments are essential for clinical monitoring and research. This study evaluated the psychometric properties of a modified medication adherence scale designed to better capture adherence behaviors among PLHIV across diverse clinical settings. Methods: A cross-sectional multisite study involved 342 PLHIV receiving ART at three HIV treatment centers. The modified instrument comprised eight items adapted from established adherence scales to incorporate behavioral and contextual factors affecting adherence. Content validity was assessed through expert panel review, and construct validity was examined using exploratory factor analysis (EFA). Internal consistency reliability was evaluated using Cronbach’s alpha, and item-total correlation analysis assessed individual item performance. Results: The instrument demonstrated satisfactory psychometric properties. Content validity indices were high (I-CVI range: 0.83– 1.00), indicating strong expert agreement. EFA revealed a two-factor structure representing unintentional and intentional non-adherence, explaining 62.4% of the total variance. The overall scale showed good internal consistency reliability with a Cronbach’s alpha of 0.82. Conclusion: These findings indicate that the modified medication adherence scale is a reliable and valid instrument for assessing ART adherence among PLHIV and may be useful for clinical assessment and research applications.